KANO 모델 기반 반려동물 헬스케어 APP UX 디자인 연구 - 황슈월(SHUYUE HUANG), 잠심(QIN CEN), 정의태(Euitay Jung) (한국디자인리서치, 2025)
반려동물 건강에 대한 양육자의 관심이 증대됨에 따라 반려동물 의료 산업은 높은 성장 잠재력을 보이고 있다. 그러나 핵심 서비스 단계 중 하나인 반려동물 헬스케어 APP은 의료 서비스 경험과 건강 관리 측면에서 사용자 개인화 요구를 충분히 충족하지 못하는 한계를 지닌다. 본 연구는 이러한 문제를 해결하기 위하여 KANO 모델과 Better-Worse 민감도 분석을 통합하여 사용자 기능 요구의 우선순위를 체계적으로 규명하고, ‘요구 도출–속성 분류–디자인 전환’의 단계적 연구 방법을 제시하였다. 실증 분석 결과, ‘온라인 약품 구매 및 배송’, ‘건강 기록 관리’, ‘진료 예약’ 기능이 핵심적 중요성을 지니는 것으로 확인되었다. 이를 토대로 네 가지 핵심 모듈을 중심으로 ‘AI 건강 제안’, ‘원격 영상 모니터링’, ‘건강 알림’과 같은 혁신적 기능을 포함한 인터페이스 시안을 설계하였다. 만족도 평가에서는 기능 적합성, 전문성 신뢰도, 구조적 명확성이 사용자 행동 의도에 긍정적 영향을 미치는 것으로 나타났다. 본 연구는 반려동물 헬스케어 APP의 사용자 경험을 향상시키기 위한 실증적 근거를 제공하며, 사용자 중심의 디지털 헬스케어 플랫폼 구축에 기여할 수 있는 학문적·실무적 의의를 지닌다. As pet owners' concern for animal health increases, the pet healthcare industry shows substantial growth potential. Yet, pet healthcare applications still fall short in meeting personalized needs in medical services and health management. This study applies the KANO model and Better-Worse sensitivity analysis to prioritize user requirements and propose a framework of "requirement identification-attribute classification-design transformation." Results highlight the critical importance of online pharmaceutical purchase and delivery, health record management, and medical appointment booking. Based on these, four core modules were designed with innovative features such as AI health suggestions, remote video monitoring, and health notifications. Satisfaction analysis confirmed that functional adequacy, professional reliability, and structural clarity positively affect users' behavioral intentions. The study offers empirical evidence for enhancing user experience and contributes to the development of user-centered digital healthcare platforms. KCI Citation Count: 0